The Effect of Absorption of The Heavy Metal Lead (Pb), in Depuration Media on The Quality of Seaweed Renderment - Maghfiroh, Hanifatul; Rahim, Andi Rahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to examine the effect of lead (Pb) heavy metal absorption in depuration media on the agar quality and yield of seaweed (Gracilaria sp) from local coastal waters, and to assess its potential use in industry. The research method involved analyzing six seaweed samples using atomic absorption spectrophotometry (AAS) to measure Pb content and calculate the dry matter yield. The results showed that the SB samples (SB1, SB2, SB3) did not contain detectable levels of Pb, indicating that their growing environment was relatively free from heavy metal contamination. In contrast, the SS samples (SS1, SS2, SS3) showed detectable levels of Pb, with the highest concentration in SS2 (2.65 mg/kg). The dry matter yield in the SB samples averaged around 20%, while the SS samples had a slightly higher average yield of around 21.5%. These results indicate that the SS samples had a higher dry matter content compared to the SB samples. Based on these findings, it is concluded that the SB samples are safer for industrial use due to the absence of Pb contamination, whereas the SS samples require further treatment to reduce the risk of Pb contamination. This study emphasizes the importance of regular monitoring and testing for heavy metal content in seaweed to ensure product quality and safety, as well as effective environmental management of coastal waters to prevent heavy metal contamination of vital natural resources.